Features experimentation in theater Iraqi academic: يوسف هاشم عباس (Al-Academy, 2016)
1.Chapter I (systematic framework) which includes: the research problem and the importance of the research, the need for it, the goals of the research, the temporal &spatial boundaries, determine the terms and defined procedurally.2.Chapter II - the theoretical framework: It consists of three sections are:•The first topic:- the concept of references and experimentation in the theater. •The second topic:- the director of academic and experimentation in Iraq. Two paragraphs in this section came after the introduction, in first paragraph to talk about the Iraqi theater academic and experimentation, and in the second paragraph the researcher spoke about the academic director of the Iraqi and experimentation. 3.Chapter III - Actions - the research community: - the method of selecting samples: Adoption of the way (intentional) in the selection of specimens. 4.Chapter IV - Results and conclusions:- (results, conclusions, proposals, recommendations, list of sources and references, appendices, abstract in English).